New adhesive protocol improves shear bond strength of Polyetherketoneketone (PEKK) - Arvai, Robert; Baroudi, Kusai; Duarte, Laís; Diamantino, Pedro Jacy Santos [UNESP]; Gimenez, Mariana Gadelho [UNESP]; Phillippi, Analucia Gebler; Saavedra, Guilherme de Siqueira Ferreira Anzaloni [UNESP]; Waghon, Zuila Maria Lobato; Gonçalves, Thais Marques Simek Vega (Elsevier, 2024)
Objective: Inert surface of Polyetherketoneketone (PEKK) jeopardizes resin bonding. This study aimed to present a new adhesive protocol to improve PEKK bonding. Methods: A total of 360 PEKK blocks were milled, polished (maximum roughness of 0.20 µm), and randomly assigned to groups. The new protocol was applied (n = 36) and compared to conventional treatments (no treatment; sandblasting (110-µm Al2O3 and silica); no adhesive; Visiolink (Bredent); and PEKKbond (AnaxDent)) (n = 36). For the new protocol, the surface was blasted (110 µm Al2O3 and 96% isopropyl alcohol at 60 psi), followed by 96% isopropyl alcohol washing, and air drying. PEKKbond was applied (dried for 3 min at 77 °C), followed by Visiolink (dried for 3 min at 60 °C); both light-cured for 3 min (800 mW/cm2). Preopaque (GC Europe) and Opaque (AnaxDent) were applied and light-cured (5 min). Morphological topography was analyzed, and flowable gingiva-colored composite (AnaxGum, AnaxDent) was bonded. All specimens were aged for 24 h and thermocycled (5000 cycles, 5–55 °C). Shear bond strength (SBS) was measured (MPa) and data were analyzed by two-way ANOVA, Tukey, and Weibull moduli estimation (α = 0.05). Results: The highest SBS values were found in the new protocol (p < 0.05), regardless of aging. Thermocycling reduced SBS (p < 0.05), while Al2O3 and PEKKbond produced higher SBS values than silica and Visiolink, respectively (p < 0.05). Significance: The new protocol strongly improves PEKK adhesiveness, and this can reflect in the longevity of prostheses.
Keywords: Bonding; Esthetic dentistry; Material science; Polyetherketoneketone; Polymer; Polymers